Artificial Composite Anode Comprising High‐Capacity Silicon and Carbonaceous Nanostructures for Long Cycle Life Lithium‐Ion Batteries. Issue 1 (26th February 2018) - Breitung, Ben; Schneider, Artur; Chakravadhanula, Venkata Sai Kiran; Suchomski, Christian; Janek, Jürgen; Sommer, Heino; Brezesinski, Torsten
Abstract: The use of functional nanomaterials is a common strategy to improve the mechanical and electrochemical properties of silicon anodes for secondary lithium‐ion cells. Here, we report the preparation of a structurally stable composite material with a unique morphology comprising small‐size silicon particles and especially branched carbonaceous nanofibers and the analysis of its cycling performance by galvanostatic measurements. This two‐phase composite was obtained from pyrolysis of blended silicon/cyanamide powders. The conversion of cyanamide to turbostratic carbon, rather than graphitic carbon nitride, was unexpected and appears to be catalyzed by accidental iron nanoparticles. Although the carbon content after pyrolysis was only about 7 %, half‐cells using electrodes containing the silicon/carbon composite outperformed other silicon‐based anode materials tested herein in terms of cyclability. After 300 cycles, they delivered two times higher capacity (>1.7 A h gsilicon −1 at C/10 and >0.5 A h gsilicon −1 at 1C in the 600–30 mV range when operated in constant current mode) than cells of similar loading with pristine silicon particles. The average fade rate per cycle was around 0.1 % between the 10th and 300th cycles, which is notable considering that the electrode structure and composition have not yet been optimized for battery applications. Abstract : Long live the battery : A structurally stable anode nanocomposite with a unique morphology comprising silicon particles of average size ≤50 nm and especially branched carbonaceous fibers synthesized by pyrolysis of silicon/cyanamide blends is presented. This new two‐phase material has promising properties toward next generation lithium‐ion batteries.